Analysis of Slum Management Plan in East Area Covering Medan Area and Medan Denai District - Ruth Oldrina Margareth Tobing; Achmad Delianur Nasution; Ami Marisa Lubis (Budapest International Research and Critics University, 2021)
This research is based on the need to analyze the planning of handling slums in Medan where in SK slums in 2018 the slum area of Medan City is 200,292 ha but then in 2020 with the renewal of SK Kumuh increased to 819.80 Ha. The Eastern District of Medan Area and Medan Denai are part of the slums of Medan City which has a slum area of 73.74 ha needs to be analyzed to obtain proper planning so that the budget for handling slums in the area is effective and efficient. For the efficiency and effectiveness of the slum handling budget is done by analyzing 8 (eight) indicators. To obtain influential indicators and priorities of handling 8 (eight) indicators are carried out with several approaches, namely field observation and Analytical Hierarchy Process (AHP) method by analyzing questionnaires given to informants of this research, namely 10 (ten) Government Representatives and 10 (ten) Community Representatives and strengthened by secondary data that is then described qualitatively. Based on the results of the analysis obtained that 8 (eight) indicators analyzed have an effect on the Slum Management Plan in the East because all these indicators have problems that create slums and AHP results show that both government representatives and community representatives agree drainage and waste as a priority indicator of initial handling and Fire Protection and WasteWater as the last handling so that the planning of handling slums in the Eastern Region in the top - down and bottom - up is the same.